Atractylenolide-I prevents abdominal aortic aneurysm formation through inhibiting inflammation - Chen, Shuxiao; Liu, Xiaotian; Zhou, Xincheng; Lin, Weixiao; Liu, Minting; Ma, Haoran; Zhong, Keli; Ma, Qiming; Qin, Chengjian (Frontiers in Immunology, 2025)
BackgroundAbdominal aortic aneurysm (AAA) is a degenerative disease with high mortality. Chronic inflammation plays a vital role in the formation of AAA. Atractylenolide-I (ATL-I) is a major bioactive component of Rhizoma Atractylodis Macrocephalae that exerts anti-inflammatory effects in various diseases. The purpose of this study is to investigate the role of ATL-I in the progression of AAA.MethodsAAA was constructed in C57BL/6 mice by porcine pancreatic elastase (PPE)-incubation, and the diameter of the aorta was measured by ultrasound. ATL-I was administered by gavage on the second day after modeling to explore its significance in AAA. The pathological and molecular alteration was investigated by immunostaining, ELISA, qRT-PCR and Western blotting.ResultsATL-I inhibited the dilatation of the abdominal aorta and decreased the incidence of AAA. ATL-I alleviated the infiltration of macrophages in the adventitia and reduced the levels of proinflammatory factor IL-1β and IL-6 in the aorta and circulatory system, while increasing the expression of anti-inflammatory factor IL-10. Moreover, ATL-I restrained loss of smooth muscle cells and elastic fiber degradation by suppressing MMP-2 and MMP-9 expression. Mechanistically, phospho-AMPK expression was elevated in AAA groups, and ATL-I administration suppressed its expression to improve the pathological damage of aorta.ConclusionsATL-I meliorated vascular inflammation by targeting AMPK signaling, ultimately inhibiting AAA formation, which provided an alternative agent for AAA treatment.